A Comparative Study to Assess the Impact of Maternal Anaemia on Placenta Weight and Foetal Well-Being, in a Selected Tertiary Care Hospital, Chengalpattu District, Tamil Nadu, India - Karpagavalli, G.; Monickaraj, Joselly; Rani, D. Subitha (Journal of Neonatal Surgery, 2025)
Background of the study: Anaemia is the most common blood disorder that may occur during pregnancy. It has varied prevalence, etiology and degree of severity in different populations, being more common in non-industrialized countries. Anaemia is responsible for approximately 40% of maternal deaths in third world countries. It causes direct as well as indirect deaths due to cardiac failure, haemorrhage, infection and pre-eclampsia. Methodology: Quantitative exploratory research approach was selected to assess the placental weight and fetal wellbeing among anaemic and non-anaemic pregnant women. An analytical cross-sectional design was selected for this study. Eighty two pregnant women (41 anaemic and 41 non-anaemic women), who visited the labor ward at Chrompet government hospital, Tamil Nadu, India were selected. A structured interview schedule was used to collect the demographic, placental and fetal characteristics. Comparison of the impact of maternal anaemia on placental weight and fetal wellbeing among anaemic and non-anaemic pregnant women was done. Result and analysis: The comparative study reveals an evident statistically significant association between the placental weight and neonates birth weightamong non-anaemic pregnant women (χ2 = 17.680) at p < 0.05, which indicates that the placental weight gain has successfully influenced the birth weight of the newborn among non-anaemic pregnant women, while this association was not statistically significant among the anaemic pregnant women (χ2 = 9.938) as low haemoglobin levels have hindered the effective weight gain of the placenta and thereby birth weight of the newborn. There exist a positive correlation between the placental weight and neonate’s birth weight among anaemic and non-anaemic pregnant women which indicates that adequate weight gain of the placenta has a direct effect on the fetal weight gain and vice-versa among anaemic and non-anaemic pregnant women. Conclusion: The study concludes that the level of haemoglobin has a positive correlation and significant association with the placental weight and birth weight of newborn which indicates that maintenance of normal haemoglobin is essential for the normal growth and development of the placenta which proportionately influences the growth of the baby. Among mothers for whom this scenario was not met it was evident that there was a vice-versa effect on the placental weight and birth weight of newborn due to low haemoglobin level. The maintenance of maternal health must ideally begin much before the childbearing age and continue further through the postpartum period in order to prevent various complications pertaining to anaemia.